Impacts of the macro environment on airline performances in southern Africa: Management perspectives. (October 2019) - Mhlanga, Oswald
Due to the nature of the airline industry, the performance of airlines is generally affected by a combination of macro-predictability, micro-uncertainty and macro environmental factors. However, airlines in southern Africa have struggled to identify strategies to overcome these challenges resulting in a high failure rate. The purpose of this study is to identify the impacts of the macro environment on airline performances in southern Africa. A quantitative method research design was followed. Structured survey questionnaires were distributed at selected airlines to 154 key airline personnel. In order to reach the objectives of the study, exploratory factor analysis was used to identify the underlying dimensions of macro environmental factors impacting on airline performances. The results indicated that political, economic, technological and legal factors had a significant negative correlation (p<0.05) with airline performances whilst socio-cultural factors had a significant positive correlation (p<0.05) with airline performances. From the study, it is clear that the increased cost of operating airlines, government interference and overprotection of state carriers, increased competition (due to technology) and restrictive bilateral air service agreements have negatively affected airline performances in southern Africa. However, changes in passenger profile and a rise in the black middle class have positively affected airline performances. Partial and selective deregulation designed to maintain the protection of state carriers represents a considerable threat to private operators something that stifles the region's tourism prospects. To improve airline performances, southern African governments must create a level playing field for private and state carriers.